Boosting Employee Performance through Communication, Teamwork, and Discipline in Indonesia: Meningkatkan Kinerja Karyawan melalui Komunikasi, Kerja Sama Tim, dan Disiplin di Indonesia - Aulia Riza Ainun Nur Rohmah; Dewi Andriani; Kumara Adji Kusuma (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of brand ambassador, product quality, and price on consumer buying interest in Lemonilo noodles among Sidoarjo residents. Using a quantitative approach with 96 purposively sampled respondents, data was collected via Likert scale questionnaires and analyzed with SPSS 26. The findings reveal that all three factors significantly influence buying interest. Employing NCT Dream as a brand ambassador effectively attracts consumers, the product quality meets expectations, and the pricing is appropriate for the market. PT Lemonilo should maintain these strategies while exploring additional promotional activities to expand their market reach. Highlights: 1. Effective communication fosters a harmonious and organized work environment.2. Strong teamwork significantly enhances employee performance and outcomes.3. Work discipline ensures efficient and effective work processes. Keywords: Communication, Teamwork, Work Discipline, Employee Performance, PT. Zeger Indonesia